Economic burden of cancer from 2012 to 2017 based on the French national claim database (SNDS). (13th November 2019) - Verboux, D; Pestel, L; Nicolas, M; Lesuffleur, T; Rachas, A; Gastaldi-Menager, C
Abstract: Background: The aim of this study is to assess the economic burden of active cancer in France and to analyze structure and trends of expenditure between 2012 and 2017. Methods: Using information about 57 millions of individuals from the general scheme insurance database (86% of the French population) and applying 5 specifically developed medical algorithms (for lung, colon, breast, prostate and other cancers), we identified all people with active cancer. All reimbursed expenditure (hospitalization, ambulatory care, disability/sickness benefits) were extracted for each individual. To analyze trends, we applied the same methodology from 2012 through 2017. Results: In 2016 (results for 2017 will be available for the conference), among the 137 billion euros reimbursed by the general assurance scheme, 13 billion (10%) were related to active cancer and 1.2 million people were concerned (2% of the population). About 2.3 billion euros (2%) were related to breast cancer (189, 000 people), 1.4 billion euros (1%) for colon cancer (123, 000 people), 1.4 billion euros (1%) for lung cancer (77, 000 people) and 1 billion (0.8%) for prostate cancer (167, 000 people). Hospitalizations represented the main expenditure for colon (71%), lung (61%) and breast cancer (56%). Concerning prostate cancer, hospitalizations stood for 36% while ambulatory care represented 62%. From 2012 to 2016, the expenditure related to active cancer increase by 4.4%/year due to both an increase in patients and in the average annual cost per patient (both +2.2% per year). Focusing on breast cancer, average expenditure increased by 3.2% per year from 10, 700€ per year per patient to 12, 200€ per year per patient. Conclusions: Our study demonstrates the high economic burden of active cancer in France with a detailed analysis of expenditures. The developed tool will help to monitor the burden of these diseases and to implement public health policies. Key messages: Active cancers account for a significant proportion of healthcare expenditure in France. Knowing this weight allows designing and implementing public policies adapted to the situation.